The safety and efficacy of TACE combined with HAIC, PD-1 inhibitors, and tyrosine kinase inhibitors for unresectable hepatocellular carcinoma: a retrospective study - Huang, Zhongjing; Wu, Ziyi; Zhang, Lidong; Yan, Likun; Jiang, Hai; Ai, Junhua (Frontiers in Oncology, 2024)
Objective：To assess the effectiveness and safety of transarterial chemoembolization (TACE) in combination with hepatic artery infusion chemotherapy(HAIC)、PD-1 inhibitors，and tyrosine kinase inhibitors(TKI) for unresectable hepatocellular carcinoma (HCC).Methods：A retrospective analysis was performed on 158 unresectable HCC patients admitted to the First Affiliated Hospital of Nanchang University between May 2019 and October 2022. The patients were split into two groups based on the type of treatment they received: TACE combined with HAIC,PD-1 and TKI group (THPK) and TACE combined with PD-1 and TKI group (TPK). The response was evaluated using modified solid tumor Efficacy Assessment Criteria (mRECIST).Kaplan-Meier curves were used to analyze the overall survival (OS). OS-influencing factors were identified using the Cox proportional risk regression model.Results：Finally, 63 patients who received THPK treatment and 60 patients who had TPK treatment were included. The THPK group had higher DCR (77.78% vs. 55.00%, P=0.007) and ORR (20.63% vs.13.34%, P=0.282) than the TPK group did. The survival analysis curve also showed that the median OS was substantially longer in the THPK group than in the TPK group (OS: 21 months vs. 14 months, P=0.039). After multivariate Cox regression-corrected analysis, extrahepatic metastases (P=0.002) and methemoglobin >400 (P=0.041) were adverse influences on OS, but the THPK group (relative to the TPK group) was an independent favorable prognostic factor for OS (P=0.027). The results of the subgroup analysis showed that the addition of HAIC therapy to TPK treatment in patients with BCLC stage C, age ≦60 years, ECOG grade 0 and lobular distribution of tumors prolonged overall survival time and improved prognosis. Except for nausea, there was no difference in the adverse events between the two groups.Conclusion：In patients with unresectable HCC, the THPK group had a longer OS and similar adverse events compared to the TPK group. In the future, TACE-HAIC in combination with targeted and immunotherapy may be a more effective therapeutic option for hepatocellular carcinoma that cannot be surgically removed.